Archaeology of food an encyclopedia - Metheny, Karen Bescherer 1960- (Lanham, Maryland Rowman & Littlefield, 2015)
"This indispensable resource provides an illustrated introduction to and overview of the archaeological study of food and foodways today"--Provided by publisher.
Volume 1: A-K -- volume 2: L-Z.
Includes bibliographical references and index.
Keywords: Prehistoric peoples -- Food -- Encyclopedias; Food habits -- History -- Encyclopedias; Diet -- History -- Encyclopedias; Excavations (Archaeology) -- Encyclopedias; Social archaeology -- Encyclopedias